2015
DOI: 10.1614/wt-d-14-00095.1
|View full text |Cite
|
Sign up to set email alerts
|

Tank Mixing Pendimethalin with Pyroxasulfone and Chloroacetamide Herbicides Enhances In-Season Residual Weed Control in Corn

Abstract: Kochia, common lambsquarters, and wild buckwheat are major problem weeds in glyphosate-resistant corn production in the northern Great Plains of the United States. Field research was conducted in 2011 and 2012 near Huntley, MT to investigate effective PRE herbicides applied alone or in premixes with or without tank-mixed pendimethalin for extended in-season residual control of the selected broadleaf weeds in glyphosate-resistant corn. Control of kochia, common lambsquarters, and wild buckwheat with recently re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 26 publications
4
14
0
Order By: Relevance
“…Dimethenamid-P alone and S-metolachlor alone were the least effective treatments for kochia control in safflower across all evaluation dates (<20% control). Similarly, in a study conducted in corn, the end-season kochia control with dimethenamid-P or acetochlor (another chloroacetamide herbicide) did not exceed 32%; however, the addition of pendimethalin to acetochlor significantly improved kochia control [14].…”
Section: Kochia Controlmentioning
confidence: 89%
See 1 more Smart Citation
“…Dimethenamid-P alone and S-metolachlor alone were the least effective treatments for kochia control in safflower across all evaluation dates (<20% control). Similarly, in a study conducted in corn, the end-season kochia control with dimethenamid-P or acetochlor (another chloroacetamide herbicide) did not exceed 32%; however, the addition of pendimethalin to acetochlor significantly improved kochia control [14].…”
Section: Kochia Controlmentioning
confidence: 89%
“…Among all PRE herbicide treatments, there was a greater decline in kochia control with pyroxasulfone alone (low or high rate) or pendimethalin alone [14]. Dimethenamid-P alone and S-metolachlor alone were the least effective treatments for kochia control in safflower across all evaluation dates (<20% control).…”
Section: Kochia Controlmentioning
confidence: 92%
“…As such, when tank-mixed, common lambsquarters control was increased when sulfentrazone was added to pyroxasulfone, but there was no benefit of adding pyroxasulfone to sulfentrazone. Similarly, Jha et al (2015) found that application of pyroxasulfone did not provide acceptable control of common lambsquarters in corn. Mahoney et al (2014a) also reported common lambsquarters control as low as 19% with pyroxasulfone at 89 g a.i.…”
mentioning
confidence: 99%
“…ha (1 sulfentrazone was sufficient to provide soybean yields that were 90% of the weed-free control. Jha et al (2015) evaluated pyroxasulfone and chloroacetamide herbicide combinations and found that corn yields were consistently higher for tankmixed treatments relative to individual application.…”
mentioning
confidence: 99%
“…In other studies, Jha et al [21] (Table 5). Wild mustard density and aboveground dry weight were generally similar to the weedy plots for both crops, except in soybean in which density was reduced 83% with pyroxasulfone ( Table 5).…”
Section: Redroot Pigweedmentioning
confidence: 80%